Preferences and adoption of improved cookstove from results-based financing program in Southeastern Ethiopia - Belachew, Azmera; Melka, Yoseph (Frontiers in Energy Research, 2023)
Environment-friendly energy practices are essential for a sustainable and quality environment in most developing countries, like Ethiopia. To achieve this, result-based financing (RBF) was implemented to distribute ICS with a demand and supply side management system. However, the success of RBF is not evaluated regarding households’ preferences and adoption of the stove. This study was conducted to evaluate households’ preference and adoption of improved Tikikil stove in the RBF implementation areas. Data were collected from 191 households using a household survey and 10 focus group discussions. The data were analyzed using descriptive statistics and a binary logit regression model using STATA 16 software. The result revealed that the cost of stove, stove holding, construction material, cooking time reduction, and smoke reduction were the top five attributes ranked by user households. The dissatisfied households have complained about durability, wood inlet size, stove cost, and suitability of pot size. Results also indicated that the success of the RBF program showed moderately effective. The regression result revealed that education, family size, landholding size, livestock holding, fuel expenditure, awareness, and separate kitchen were significantly and positively associated while distance to nearest town is significantly and negatively related to the adoption of Tikikil stove. The findings suggest that households need Tikikil stove options to reduce the negative effect of traditional stoves but currently available stoves lack to address the preferences of the households. In addition, different socio-economic characteristics of households and stove attributes are important factors that need to consider for the wider adoption of ICS.